Development of a hepatitis B virus carrier transgenic mice model [Hepatit B virusu taşιyιcιsι transgenik fare modelinin geliştirilmesi] - (:unkn) unknown (My University, 2008)
The studies for the development of transgenic mice models which provide important profits for the studies concerning immunopathogenesis of hepatitis B virus (HBV) infections are in progress since 20 years. For this purpose different lineages bearing whole HBV genome or selected viral genes have been developed and their usage in clarifying the HBV replication and pathogenesis mechanisms have been emphasized. The aim of this study was to develop and breed a HBV carrier mice model. In the study the full HBV genome has been transferred to mouse embryos by microinjection procedure. Following transgenic manipulation, the HBV carriers among the daughter mice have been detected by molecular methods in which HBV-DNA replication and expression have been shown. The manipulations for transgene transfers have been performed in TUBITAK Marmara Research Center Transgene Laboratory, Gebze, İstanbul. The HBV-DNA carrier mice have been demonstrated by polymerase chain reaction (PCR) using the DNA samples obtained from tail tissues and also by dot-blot hybridization of the mice sera. Integrated HBV-DNA has been detected by applying in-situ hybridization to the liver tissue sections. HBV-DNA expression has been shown by reverse transcriptase PCR method with total RNA molecules that have been isolated from the liver tissues of the HBV-DNA carrier mice. HBsAg has been detected in the liver by immunohistochemical method, and HBsAg and HBeAg have additionally been demonstrated by ELISA. HBV genome, expression of the genome and the expression products have been determined in approximately 10% of the mice of which HBV-DNA have been transferred. By inbreeding heterozygote carrier mice, homozygote HBV transgenic mice line have been obtained. These HBV transgenic mice are the first lineages developed in our country. It is hopefully thought that this HBV carrier transgenic mouse model may contribute to the studies on the pathogenesis of HBV infections which are important health problems in the world as well as in Turkey.
Keywords: HBV carrying transgenic mice; HBV infection